Quantifying solvent action in oil paint using portable laser speckle imaging - Baij, Lambert; Buijs, Jesse; Hermans, Joen J.; Raven, Laura; Iedema, Piet D.; Keune, Katrien; Sprakel, Joris (Scientific reports, 2020)
The exposure of oil paintings to organic solvents for varnish removal or to water for the removal of surface dirt can affect the chemical and physical properties of oil paint in an undesired way. Solvents can temporarily plasticise and swell the polymerised oil paint binding medium, enhancing both the thermal mobility and mechanical displacement of pigments embedded in this film. The enhancement of these microscopic motions can affect both the chemical and physical stability of the object as a whole. In order to minimise solvent exposure during cleaning, an analytical method that can quantitatively measure the microscopic motions induced by solvent uptake, is required first. In this study, we use Fourier Transform Laser Speckle Imaging (FT-LSI) and a newly developed portable FT-LSI setup as highly resolved motion detection instruments. We employ FT-LSI to probe pigment motion, with high spatiotemporal resolution, as a proxy for the destabilising effects of cleaning solvents. In this way, we can study solvent diffusion and evaporation rates and the total solvent retention time. In addition, qualitative spatial information on the spreading and homogeneity of the applied solvent is obtained. We study mobility in paint films caused by air humidity, spreading of solvents as a result of several cleaning methods and the protective capabilities of varnish. Our results show that FT-LSI is a powerful technique for the study of solvent penetration during oil paint cleaning and has a high potential for future use in the conservation studio.